Institutional Synergism as the Information Center for Agriculture Development (PIPP) in Indonesia - Alif, muhammad; Oktarina, Selly; Zainal, Anna Gustina (JASSP, 2021)
Institutional empowerment will push the improvement of farmer productivity which can affect the well-being of farmer life. The purpose of this article is to determine the role of institutions in the development of the Center for Agricultural Development Information in rural and the efforts that can be made to create synergy between institutions and PIPP. This paper uses a literature review by looking for relevant references according to existing problems. The data has been obtained are then analyzed using descriptive analysis methods. The results and discussion show that some of the institutions involved in the Agricultural Development Information Center (PIPP) are, universities, local governments, opinion leaders, non-governmental organizations (NGOs), farmer organizations (extension agents, farmer contacts, farmer group associations, (Gapoktan) and farmer groups). Empowering farmers through common perceptions and alignment of goals, strengthening institutions for the continuity and sustainability of resources and structuring institutional capacity, improving institutional management, improving leadership patterns, and transparency.